A study on cognitive metaphors denoting the concept of "War" and "Peace" in anti-war songs in English versus Vietnamese - Nguyễn Thị Hồng Mến (The University of Da Nang, 2014)
Introduction; Literature review and theoretical background; Research design and methodology; ...